ASFS presidential address 2018: Towards an epistemology of pleasure and a post-liberal politics of joy. (1st January 2019) - Ray, Krishnendu
ABSTRACT: At this moment of great peril for democracies across the world, scholars must not only be critical but develop affective investment in common people's lives so as to be able to engage in the democratic process more successfully. That entails paying attention to common joys and pleasures as much as to suffering.